Controlling the Innovative Supply Chain Activities for Improving the Competitive Ability of Companies - Larisa V. Yurieva; Marina A. Kazakova (International Journal of Supply Chain Management, 2018)
As part of the supposed approach to strengthen the competitive capacity of industrial companies based on the implementation of the control of innovative activities in the supply chain, the flexible evaluation system was developed, differentiated according to the strategic and tactical objectives of the existing growth of competitive capacity. The strategic management of innovation process supposes achievement of competitive advantages based upon maximal usage of the experience of innovative supply chain activity organization and accounting of new factors, which influence on their change. To solve this problem have been analyzed conditions that determine the appearance and replace the six models of innovative process, allocated based on the modern world scientific experience. The logic of their development allows us to see the important characteristics of their changes, explain the effectiveness of the change process models, through the manifestation of the cumulative and complementary effects. The authors proposed a system of indicators to monitor the degree of manifestation of these effects in the study. In the course of the calculations have been identified changes in the patterns of the innovation process in the Russian mining and metallurgical complex and at the same time as there was a cumulative and complementary effect in changing patterns, and thus the efficiency of controlling innovation. The results suggest that the implementation of controlling innovation in mining and metallurgical enterprises cannot be called successful. Sustained growth was observed on single indicators. In mass production, they have a high degree of variability, or a downward trend. Nowadays, there are a few number of Innovative companies. Keywords- companies, innovation processes, supply chain activity, indicators, competitive ability.